Odpowiedź :
4(y +1)² – 2(1 – 2y)² + (2y – 3)(3 + 2y)/1
jeśli y =4
4(y +1)² – 2(1 – 2y)² + (2y – 3)(3 + 2y)/1=
4(y²+2y+1)- 2(1-4y+4y²)+ 6y+4y²-9-6y/1=
4y²+8y+4-2+8y-8y²+6y+4y²-9-6y/1=
16y-7/1=
16*4-7/1=
64-7/1=
57/1=
57
jeśli się nie mylę ;)
jeśli y =4
4(y +1)² – 2(1 – 2y)² + (2y – 3)(3 + 2y)/1=
4(y²+2y+1)- 2(1-4y+4y²)+ 6y+4y²-9-6y/1=
4y²+8y+4-2+8y-8y²+6y+4y²-9-6y/1=
16y-7/1=
16*4-7/1=
64-7/1=
57/1=
57
jeśli się nie mylę ;)
4(y +1)² – 2(1 – 2y)² + (2y – 3)(3 + 2y)= 4y²+4²-2²+4y²+6y+4y²-9-6y=
= 4y²+16-4-9+4y²+6y+4y²-6y= 12y²+3= 12(4²)+3= 12×16+3= 192+3 =195
= 4y²+16-4-9+4y²+6y+4y²-6y= 12y²+3= 12(4²)+3= 12×16+3= 192+3 =195
4(y²+2y+1)-2(1-4y+4y²)+4y²-9=
4y²+8y+4-2+8y-8y²+4y²-9=
16y-7=64-7=57
4y²+8y+4-2+8y-8y²+4y²-9=
16y-7=64-7=57